Isothiocyanate-rich moringa seed extract reduces skin inflammation in mouse ear edema model - Khea Wolff; Keyaara Robinson; Nanjoo Suh; Bozena Michniak-Kohn; Michael Goedken; Marianne Polunas; Ilya Raskin (Elsevier, 2023)
Background: Moringa (Moringa oleifera Lam.) seed extract (MSE) and its primary bioactive compound, moringa isothiocyanate-1(MIC-1), mitigate inflammation, oxidative stress, diabetes, and cancer in the in vivo rodent models following oral application. Purpose: To investigate the topical anti-inflammatory activity of MSE and purified MIC-1 in a TPA-induced mouse ear edema model. Study Design: The present study elucidates the topical anti-inflammatory effects and mechanisms of action of MSE, containing 38% of MIC-1 and purified MIC-1 using a mouse ear edema model utilizing 12-O-tetradecanoylphorbol-13-acetate (TPA), as the pro-inflammatory agent. Methods: A time-dependent and dose-dependent response was determined by pretreating CD-1 mice with various doses of MSE and MIC-1, positive control, dexamethasone, or vehicle control, followed by TPA, and the subsequent difference in ear thickness was measured using digital Vernier calipers. The effective doses of MSE and MIC-1were then selected to evaluate the change in weight of the ears using 6 mm biopsy punches and the results were confirmed by microscopy. Inflammatory markers were quantified with Luminex multiplex immunoassay. Results: MSE and MIC-1 were effective in a dose-dependent manner in a TPA-induced ear edema model, causing a reduction in ear thickness and a 48% and 49% decrease in ear punch weight, respectively. MSE and MIC-1 also caused a reduction in the levels of cytokine and chemokines, interleukin 6 (IL-6), monocyte chemoattractant protein-1 (MCP-1), and keratinocyte chemoattractant (KC) in the ear tissue. MSE and MIC-1 reduced IL-6 expression by 84% and 78%, MCP1 by 74% and 73%, and KC by 56% and 43%, respectively. Additionally, the anti-inflammatory effect of MSE and MIC-1 was confirmed by hematoxylin and eosin (H&E) staining, used to assess the thickness of the ear swelling. MSE significantly reduced the thickness of the ears by 20% compared to TPA. Conclusion: These results reveal the topical anti-inflammatory properties of MSE, and MIC-1 likely transmitted via the nuclear factor erythroid 2-related factor 2 (Nrf2) and nuclear factor-kappa B (NF-κB) pathways as mentioned in previous studies. This work also suggests therapeutic uses of MSE and/or MIC-1 for skin inflammation.